2005
DOI: 10.1111/j.1745-7254.2005.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase II metabolites of etofesalamide in filamentous fungi1

Abstract: Aim: To study phase II metabolites of etofesalamide in filamentous fungi. Methods: Seven fungi were screened to transform etofesalamide. The metabolites of etofesalamide were assayed using liquid chromatography coupled to mass spectrometry. The major metabolite was subject to enzymatic hydrolysis to confirm its structure. Results: Etofesalamide was converted into two phase II metabolites: glucoside and riboside conjugates. Glucoside conjugate was the major product with a yield greater than 90%; no phase I meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As shown in Figure 3, 5 of the metabolites were essentially similar to those obtained in mammalian metabolism studies, whereas 2 novel metabolites, N-desalkylmetoprolol and the glucoside conjugate of O-desmethylmetoprolol, were identified. It has been well recognized that conjugation is an important metabolic pathway of many compounds both in mammals and in microorganisms [16][17][18] . A glucoside conjugate was detected in the present study, which conformed to previous studies that the glucosidation of drugs can be formed by microbial models [10,18,19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3, 5 of the metabolites were essentially similar to those obtained in mammalian metabolism studies, whereas 2 novel metabolites, N-desalkylmetoprolol and the glucoside conjugate of O-desmethylmetoprolol, were identified. It has been well recognized that conjugation is an important metabolic pathway of many compounds both in mammals and in microorganisms [16][17][18] . A glucoside conjugate was detected in the present study, which conformed to previous studies that the glucosidation of drugs can be formed by microbial models [10,18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been well recognized that conjugation is an important metabolic pathway of many compounds both in mammals and in microorganisms [16][17][18] . A glucoside conjugate was detected in the present study, which conformed to previous studies that the glucosidation of drugs can be formed by microbial models [10,18,19] . In humans, metoprolol was metabolized to O-desmethylmetoprolol and metoprolol acid or α-hydroxymetoprolol, depending on the cytochrome P450 oxidation phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the amino acid sequences of CTs are very similar [ 49 ], their biological activity can differ significantly [ 50 , 51 ]. Most studies have shown that CTs begin to act even at a concentration of less than 1 μM, initially causing an increase in contraction, followed by a decrease and a concomitant rise in the resting tension [ 9 , 52 , 53 ]. Comparison of various myocardial tissues showed that the effect of CTs on the ventricular tissue is more pronounced than that on the atria [ 54 , 55 ].…”
Section: Snake Venoms: Composition and Propertiesmentioning
confidence: 99%
“…Several studies have investigated the biotransformation of drugs by fungi [11][12][13][14][15][16][17][18][19] and it has been shown that some of these organisms produce mammalian metabolites. [11,[14][15][16][17][18][19] Examples of metabolic transformations in Cunninghamella fungi are the phase I reactions hydroxylation, [14] epoxidation, [14] N-oxidation, [20] N-dealkylation, [15] O-demethylation, [15] and deamination, [15] as well as the phase II reactions glucuronic acid conjugation, [21] sulfate conjugation, [21] glucoside conjugation, [13] and riboside conjugation. [13] This fungal genus has been found to express either a cytochrome P450 [22] or a similar enzymatic system.…”
mentioning
confidence: 99%
“…[11,[14][15][16][17][18][19] Examples of metabolic transformations in Cunninghamella fungi are the phase I reactions hydroxylation, [14] epoxidation, [14] N-oxidation, [20] N-dealkylation, [15] O-demethylation, [15] and deamination, [15] as well as the phase II reactions glucuronic acid conjugation, [21] sulfate conjugation, [21] glucoside conjugation, [13] and riboside conjugation. [13] This fungal genus has been found to express either a cytochrome P450 [22] or a similar enzymatic system. [23] Cytochrome P450 enzyme systems mediate the metabolism of many compounds in mammals [24] and thus Cunninghamella fungi can be used to mimic mammalian drug metabolism.…”
mentioning
confidence: 99%